VD_FINDINFO Jug / 2014 / 291 vom 25. März 2014 - VD Tribunal cantonal (2014)
FIXATION DE LA PEINE, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE, SURSIS À L'EXÉCUTION DE LA PEINE, FRAIS JUDICIAIRES | 42 CP, 43 CP, 47 CP, 426 al. 1 CPP (CH)